Alterações neuroanatômicas e funcionais do sistema respiratório no sono e na vigília em um modelo experimental para doença de Alzheimer - Vicente, Mariane Cristine (2021)
The dysfunction of the respiratory system is seen in several neurodegenerative diseases such as Alzheimer's, but how the pathophysiology mechanisms of the disease are related to the respiratory system remains poorly documented. Here, we treat animals with intracerebroventricular streptozotocin (STZ, 2 mg / kg). In chapter 1, we measured ventilation (VE), electroencephalography and electromyography during normocapnia, hypercapnia and hypoxia in Wistar rats. In addition, we performed western blot analyzes for phosphorylated tau, total tau and amyloid- (Aβ) peptide at the locus coeruleus (LC), retrotrapezoid nucleus (RTN), medullary raphe, pre-B¨otzinger / B¨otzinger complex and hippocampus, and we evaluated memory acquisition and learning using Barnes' maze. The STZ-DA model increased the ventilatory response in hypercapnia by 26% during wakefulness due to the increase in tidal volume, but no change in VE was observed in room air or ihypoxia conditions. We observed an increase of 93% in the percentage of awake-state time during room air in the STZ model. And, we associate the results to the 73% increase in amyloid beta peptide in the LC region. In order to analyze the electrophysiological properties and sensitivity of LC neurons during hypercapnia (10% CO2, pH = 7) in the STZ-DA model, we performed the patch clamp technique in chapter 2. We observed that most (~ 60%) of the noradrenergic neurons of the LC in adult rats were inhibited after exposure to CO2, as indicated by a significant decrease in the action potential (AP). The STZ-DA model had a 57% higher sensitivity to CO2 compared to controls, which was partly due to the hyperpolarization of the resting membrane potential -52.2 mV. The reduction in AP in both groups was generally accompanied by lower activity of the LC network, depolarized AP threshold, increased AP repolarization and increased current through a voltage-dependent sub-population of K + channels (KV). Then, in chapter 3, we decided to take a treatment with the drug minocycline to reverse the cognitive, respiratory, sleep-awake cycle, and molecular disorders found earlier in chapter 1 in the STZ model. For that, we performed the same techniques as in chapter 1. Additionally, the animals were treated for five days with minocycline at a dose of 30 mg / kg, we analyzed the micrology cells in the LC region by immunohistochemistry for IBA-1 and the pro-inflammatory cytokines by real-time PCR. Minocycline treatment improved learning and memory, possibly due to decreased cell density and inactivation of microglia cells in the LC region, as well as decreased IL-B cytokine. However, the treatment did not reverse the increased sensitivity to CO2 during awake state in room air. Likewise, we did not observe a decrease in the expression of beta-amyloid peptide in the LC region after treatment. Our study demonstrates that the ventilatory response to CO2 is increased in the STZ model due to changes in the noradrenergic neurons of the LC, which have their electrophysiological properties altered possibly by an increase in beta-amyloid. The cognitive and sleep changes observed in the STZ model are due to changes in microglia, since the use of minocycline was able to attenuate